2001
DOI: 10.1006/dbio.2001.0290
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dally, an Integral Membrane Proteoglycan, and Its Function during Adult Sensory Organ Formation of Drosophila

Abstract: In Drosophila, imaginal wing discs, Wg and Dpp, play important roles in the development of sensory organs. These secreted growth factors govern the positions of sensory bristles by regulating the expression of achaete-scute (ac-sc), genes affecting neuronal precursor cell identity. Earlier studies have shown that Dally, an integral membrane, heparan sulfate-modified proteoglycan, affects both Wg and Dpp signaling in a tissue-specific manner. Here, we show that dally is required for the development of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 63 publications
4
64
0
Order By: Relevance
“…Previously, Fujise et al demonstrated that dally mRNA distribution was virtually identical to that observed with a dally-lacZ line (Fujise et al, 2003). dally expression in the wing pouch is induced by Hh and Wg signaling, but repressed by Dpp signaling (Fujise et al, 2001;Fujise et al, 2003). As shown in Fig.…”
Section: Dlp Forms An Inverse Gradient To the Wg Gradient And Its Expsupporting
confidence: 71%
See 1 more Smart Citation
“…Previously, Fujise et al demonstrated that dally mRNA distribution was virtually identical to that observed with a dally-lacZ line (Fujise et al, 2003). dally expression in the wing pouch is induced by Hh and Wg signaling, but repressed by Dpp signaling (Fujise et al, 2001;Fujise et al, 2003). As shown in Fig.…”
Section: Dlp Forms An Inverse Gradient To the Wg Gradient And Its Expsupporting
confidence: 71%
“…Collectively, our data argue that Dlp expression is negatively regulated by Wg signaling. Taken together with the observation that Dally is upregulated by Wg signaling at DV boundary (Fujise et al, 2001), our new results suggest that the relative contributions of Dally and Dlp in Wg gradient formation are controlled, at least in part, by their expression levels.…”
Section: Dlp Forms An Inverse Gradient To the Wg Gradient And Its Expsupporting
confidence: 71%
“…It has also been proposed that Dally is required for the stability and long-range distribution of Hh and Wg. dally mRNA expression is strong at the A/P and D/V compartment borders and uniform in the notum (Fujise et al, 2001). A Dally-YFP reporter construct shows a similar expression pattern and most likely reproduces Dally protein distribution in the wing disc (Fig.…”
Section: Both the Egf Repeats And Wd Of Shf And Wif1 Interact With Glmentioning
confidence: 72%
“…Before pupariation, Dpp is expressed in a region just anterior to the anteriorposterior compartment boundary, and this produces a gradient of extracellular Dpp that runs through most of the disc (Belenkaya et al, 2004;Teleman and Cohen, 2000). The levels of extracellular BMPs are reduced around wing disc cells that lack either the enzymes required for HS synthesis or the two Drosophila glypicans Dally and Dally-like (Dlp) (Belenkaya et al, 2004;Fujise et al, 2001). Although, in theory, the reduced accumulation of Dpp could be caused by its faster diffusion through the mutant tissue (Lander, 2007), this does not appear to be the case.…”
Section: Bmp Reception and Movement: Context-dependent Effects Of Promentioning
confidence: 99%